AKH Signaling in D. melanogaster Alters Larval Development in a Nutrient-Dependent Manner That Influences Adult Metabolism - Hughson, Bryon N.; Shimell, MaryJane; O’Connor, Michael B. (Frontiers in Physiology, 2021)
Metabolism, growth and development are intrinsically linked, and their coordination is dependent upon inter-organ communication mediated by anabolic, catabolic and steroid hormones. In Drosophila melanogaster, the corpora cardiaca (CC) influences metabolic homeostasis through adipokinetic hormone (AKH) signaling. AKH has glucagon-like properties and is evolutionarily conserved in mammals as the gonadotropin-releasing hormone (GnRH), but its role in insect development is unknown. Here we report that AKH signaling alters larval development in a nutrient stress-dependent manner. This activity is regulated by the locus dg2, which encodes a cGMP-dependent protein kinase (PKG). CC-specific downregulation of dg2 expression delayed the developmental transition from larval to pupal life, and altered adult metabolism and behaviour. These developmental effects were AKH-dependent, and were observed only in flies that experienced low nutrient stress during larval development. Calcium-mediated vesicle exocytosis regulates ecdysteroid secretion from the prothoracic gland (PG), and we found that AKH signaling increased cytosolic free calcium levels in the PG. We identified a novel paracrine signaling pathway through which PKG acts in the CC to communicate metabolic information to the PG via AKH signaling. This pathway provides a means whereby larval nutrient stress can alter developmental trajectories into adulthood.